Splinting of penis following microvascular reconstruction- A simple inexpensive method - Sharma Abhishek; Misra Ashutosh; Basu Sandip (Indian Journal of Plastic Surgery, 2009)
We present a simple method of splintage following microvascular reconstruction of penis. The splint is made by removing the bases of two thermocol glasses and joining them with paper adhesive tapes to form a hollow cylinder to protect and support the penis and keep it vertical. The splint is slid over the catheter and the reconstructed penis and fixed to the lower abdominal wall and the thighs with paper tapes for stability. A window at the base of the splint is made for the purpose of observation, while the tip is monitored from the open end at the top.